Fixed tapering dosage of acitretin in patients with psoriasis: A short-term analysis of clinical efficacy and its effects on biochemical parameters - Varadraj V Pai; Diksha Phadke; Pankaj Shukla; Krupeksha Naik (Wolters Kluwer Medknow Publications, 2019)
Background: Acitretin is a widely used systemic retinoid in the treatment of psoriasis. Dosage of acitretin in not weight adjusted due to certain interindividual variations. Objective: To evaluate the clinical efficacy and effects on biochemical parameters of fixed tapering dosage of acitretin in patients with psoriasis administered over a period of 4 weeks. Materials and Methods: This was an observational study. The study included patients of psoriasis vulgaris in the age group of 18 and 65 years with a psoriasis area severity index (PASI) score of >10 which was not responsive to topical therapy and phototherapy. Patients were given oral acitretin daily at a dose of 25 mg BD for 2 weeks, which was later tapered to 25 mg OD for another 2 weeks. The clinical efficacy and biochemical parameters were assessed. Results: Out of the 18 patients, PASI 75 was achieved in 66% of the patients by the end of the third week. Significant elevations were noted in serum lipids during 4 weeks, which returned to normal limits or near baseline levels at the end of 4 weeks. Conclusion: Fixed tapering dose of acitretin is effective in psoriasis with minimal clinical and biochemical adverse events